Let . Find
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let g ( T ) = ∫ 0 T 1 + ( f ′ ( x ) ) 2 d x and h ( T ) = T . The former function is just the arc length of f ( x ) = x s i n ( x ) for the entire right half of the curve, which is the length over the entire positive reals as T tends toward infinity. Upon first observation:
l i m T → ∞ h ( T ) g ( T ) = ∞ ∞
and applying L'Hopital's Rule yields:
l i m T → ∞ h ′ ( T ) g ′ ( T ) = 1 + ( f ′ ( T ) 2 / 1 = 1 + ( T 2 T ⋅ c o s ( T ) − s i n ( T ) ) 2 = 1 + ( T c o s ( T ) − T 2 s i n ( T ) ) 2 = 1 = 1 .